Current Trend of Industry 4.0 in Logistics and Transformation of Logistics Processes Using Digital Technologies: An Empirical Study in the Slovak Republic - Patrik Richnák (Logistics)
Background: The digital transformation towards Industry 4.0 has become a necessity for businesses as it makes them more flexible, agile and responsive. Logistics is no exception, as it is constantly undergoing a significant transformation supported by revolutionary Industry 4.0 technologies that are fundamentally changing logistics processes and operations. Methods: In the construction of the paper, the following classical scientific methods were used: analysis, synthesis, induction, deduction, analogy, specification and comparison. Among the special scientific methods, the method of classification, concretisation, graphical methods, questionnaire survey and statistical methods were used. Results: The analysed enterprises perceive digital transformation in logistics. In the analysed enterprises in Slovakia, the Industry 4.0 strategy is implemented in logistics. Industry 4.0 in logistics has the largest representation in production logistics in each enterprise category. In implementing Industry 4.0 in logistics, enterprises confront the biggest barrier, namely, investment costs. Conclusions: Through one-way analysis of variance (ANOVA) and Pearson’s correlation coefficient, several significant relationships were confirmed. The significant relationship between manufacturing logistics and selected Industry 4.0 technologies was demonstrated. The significant relationship between procurement logistics and selected Industry 4.0 technologies was also demonstrated. The statistical analysis also confirmed a significant relationship between distribution logistics and the selected Industry 4.0 technologies.